Physico-chemical properties of mithun milk - MONDAL, S K; PAL, D T; SINGH, G; BUJARBARUAH, K M (The Indian Journal of Animal Sciences, 2014)
Results on the physical properties and chemical composition of mithun milk are presented. Fresh milk samples (60)from 10 mithun cows maintained at the institute's Mithun Farm were studied. The milk from mithun cows is white to creamy white, sweet with an aromatic flavour. The pH, LR at 15.5oC and density (g/ml) of mit hun milk were estimated to be 7.09 ± 0.06, 36.03 ± 0.98 and 1.023 ± 0.002 respectively. The fat content of mithun milk was 8.85 ± 0.42% and the percentage of solids-not-fat 11.48 ± 1.03%. Besides the protein (6.44 ± 0.45%), lactose (4.08 ± 0.75%) and ash (0.927 ± 0.01 %) content, the content of major mineral matters like calcium (0.088 ± 0.002%) and phosphorus (0.147 ± 0.008%) was also· estimated.